1988
DOI: 10.1177/026361748800500104
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Ethoxylated Sulfonates on Limestone

Abstract: Stastic adsorption experiments have been conducted to investigate the adsorption and precipitation behavior of various ethoxylated sulfonates from Saudi Arabian limestone samples under high-salinity (20%) and high temperature conditions (90°C). The effect of parameters such as salinity, pH, temperature, ethoxylation number, oil and alcohol addition has been investigated. Mechanisms governing surfactant adsorption on limestone are elucidated. A surfactant formulation has been designed to achieve minimum surfact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 9 publications
2
8
0
Order By: Relevance
“…The relation of decreased surfactant adsorption as ethoxylation degree increases has also been reported by several other authors, and observations for present experiments are in line with work performed previously on this subject (Celik et al 1988;Austad et al 1987Austad et al , 1992bAustad 1993;Paktinat 1991;Curbelo et al 2007). …”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…The relation of decreased surfactant adsorption as ethoxylation degree increases has also been reported by several other authors, and observations for present experiments are in line with work performed previously on this subject (Celik et al 1988;Austad et al 1987Austad et al , 1992bAustad 1993;Paktinat 1991;Curbelo et al 2007). …”
Section: Resultssupporting
confidence: 93%
“…The surfactant aggregates on the solid surface, thereby, take a more compact structure and the adsorption would increase further as hydrocarbon chains from the aqueous phase are transferred into the hydrophobic interior of the aggregates. Celik et al (1988) observed a similar relation when they investigated the adsorption of anionic surfactants with different ethoxylation degree onto limestone at 25, 50, and 90 C. Increased adsorption as the temperature increased was suggested to have been caused by the gradual desolvation of the EO chain with increasing temperature. This phenomenon increased the hydrophobicity of the surfactant aggregates that leads to enhanced surface activity of the surfactant leading to high adsorption.…”
Section: Resultsmentioning
confidence: 64%
See 3 more Smart Citations